Understanding School Voucher Program Research: A Failure of Theory or Implementation?. Issue 4 (October 2014) - Carr, Matthew; Holley, Marc; Gray, Nathan
School choice research generally indicates marginal positive effects on student achievement for at least some students. In explaining results, researchers attribute positive findings to evidence that education markets are driving schools to improve, while others see null or negative findings as evidence that markets are not an effective reform. We examine whether findings are suggestive of theory failure or program design failures. Analyzing key policy components of seven publicly funded voucher programs, we find that the structures of programs generally have half the necessary components to create market forces among schools, suggesting program design failure, not a failure of the theory.